2013
DOI: 10.3851/imp2745
|View full text |Cite
|
Sign up to set email alerts
|

Association between Systemic Inflammation and Obstructive Sleep Apnea in Men with or at Risk for HIV Infection

Abstract: Background To determine whether markers of systemic inflammation are associated with the presence of moderate-to-severe obstructive sleep apnea (OSA), and whether this association differs based on HIV and HIV treatment status. Methods HIV-uninfected men (HIV−; n=60), HIV-infected men receiving HAART (HIV+/HAART; n=58), and HIV-infected men not receiving HAART (HIV+/ No HAART; n=41) underwent polysomnograpy and measurement of plasma levels of TNF-alpha, soluble TNF-alpha receptors I and II (sTNFRI and sTNFRII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“… 26 We found a crude incidence of diabetes of 13.24 per 1000 PYFU, which is at the upper end of the range reported from cohort studies in high income countries (4.2–14.1 per 1000 PYFU). 2 , 26 28 Factors contributing to the increased risk of diabetes in people with HIV include insulin resistance due to the chronic inflammatory response to HIV infection, 29 which persists despite effective ART 29 , 30 and the effects of certain antiretroviral drugs. Our finding that the NRTIs stavudine and zidovudine were both associated with an increased incidence of diabetes has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 26 We found a crude incidence of diabetes of 13.24 per 1000 PYFU, which is at the upper end of the range reported from cohort studies in high income countries (4.2–14.1 per 1000 PYFU). 2 , 26 28 Factors contributing to the increased risk of diabetes in people with HIV include insulin resistance due to the chronic inflammatory response to HIV infection, 29 which persists despite effective ART 29 , 30 and the effects of certain antiretroviral drugs. Our finding that the NRTIs stavudine and zidovudine were both associated with an increased incidence of diabetes has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Determining which combination of these lifestyle factors is most strongly associated with inflammation could aid health care providers and researchers in developing lifestyle intervention and treatment programs that would be most effective in reducing systemic inflammation levels. This is especially true among PLWH who suffer from numerous sleep complaints [34-36] and increased inflammation, even when effectively undergoing ART treatment [42]. Therefore, future treatment or intervention studies among PLWH should incorporate components for sleep improvement and participation in physical activity to investigate avenues to reduce inflammation or disease progression (e.g., viral load).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study by Brigham and colleagues compared a sample of men who were HIV-negative with two groups of HIV-positive men (those receiving ART and those who were not). They found that plasma levels of TNF-alpha and IL-6 were higher only in those who were HIV+ with moderate to severe OSA compared to those with no OSA or mild levels of OSA independent of HIV-related covariates or treatment [42]. Other studies have shown increased plasma levels of various cytokines and markers of inflammation among PLWH regardless of ART treatment [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, lower CD4 percent was associated with poorer sleep efficiency and sleep maintenance efficacy as well as increased sleep fragmentation as reflected by higher WASO %. SDB in untreated HIV has been reported to be associated with higher HIV viral loads as well as high CRP, TNFα, TNFRII and IL-6 levels 37,38 . Even with the use of potent combination ART, HIV-associated immune activation may result in OSA via blunted neuromuscular control of the upper airway 39 .…”
Section: Discussionmentioning
confidence: 99%